Vitamin B12 Levels in Type 2 Diabetes Patients on Metformin in Gaza Strip-Palestine - Saqer, Lamia'a S.; Al-majaidah, Mohammed I.; Safi, Youssef O.; Shbair, Salem S. Shbair; Abu-Azab, Tareq Z. (RA Journal of Applied Research, 2018)
Background: Metformin is the most common oral hypoglycemic agent that used to treat Type 2 Diabetes Mellitus(T2DM) patients, which associated side effects such as Vitamin B12(VB12) deficiency. Objective: This study was carried out to determine the serum level of vitamin B12 in Palestinian patients with T2DM lived in Gaza Strip. Materials And Methods: We conducted cross sectional study comprised 73T2DM patients on Metformin. Questionnaire interview was applied. Blood samples were collected for CBC and VB12 detection. VB12 deficiency was defined as serum concentration of <300 pg/ml. Results: There was significantly lower in mean of vitamin B12 level in participants who have used metformin for ≥5years and in patients who were on metformin at a dose of ≥1000 mg/ day. Duration of metformin use were associated with increased risk of B12 deficiency 4.9 times (OR= 4.9) which increases the risk of DM complications 2.7 times . The results showed that 100 mg increase in metformin dose was associated with a 19.3 ± 4.4 pg/ ml (P = 0.00) lowering Vitamin B12 level. Every one year increase in the duration of diabetes associated with18.6 ± 6.7 pg/ ml( P =0.007) lowering in VB12 level. Conclusion : Low serum VB12 level is associated with longer duration and higher dose of metformin use. Therefore, routine determination of VB12 level in patients with T2DM on high dose of metformin and those with prolonged use of metformin might help in identifying patients that would benefit from VB12 supplements.